The ED50 and ED95 of remimazolam tosilate to inhibit the gastroscopy reaction in elderly patients of varying ages: an up-and-down sequential allocation trial - Yang, Yang; Xiong, Hao-Jing; Xu, He-Chen; Wu, Hong-Qi; Chen, Mi; Jiang, Ke; Zou, Xiao-Hua (Frontiers in Medicine, 2025)
ObjectiveAlthough remimazolam tosilate (RT) has demonstrated efficacy in elderly gastroscopy, its optimum dose for gastroscopy in elderly patients of varying ages is still unclear. The study aimed to determine the median effective dose (ED50) and 95% effective dose (ED95) of RT to inhibit the gastroscopy reaction in patients aged 65–74 years and 75–89 years.MethodsSixty-one elderly patients were randomized into two groups: Group A (65–74 years, n = 31) and Group B (75–89 years, n = 30). Three minutes after the recruited subjects received 0.1 μg/kg of sufentanil, RT was administered intravenously at an initial dose of 0.15 mg/kg with 0.01 mg/kg step size according to the modified Dixon’s up-and-down method (UDM). This continued until nine crossover midpoints “positive–negative” were observed.ResultsThe ED50 of RT calculated by the modified UDM for inhibiting the gastroscopy reaction in Group A (0.175 (95% confidence interval, CI, 0.166–0.183) mg/kg) was higher than that in Group B (0.163 (95% CI, 0.156–0.169) mg/kg) (p = 0.03). The ED95 estimated by probit regression analysis was 0.199 (95% CI, 0.186–0.244) mg/kg in Group A and 0.188 (95% CI, 0.175–0.232) mg/kg in Group B.ConclusionRT is a relatively safe sedative hypnotic that can provide a suitable sedative effect for elderly patients undergoing a gastroscopy.Clinical trial registrationhttp://www.chictr.org.cn, identifier ChiCTR2200062842.